Palmo-plantar keratoderma with debilitating pruritus - Vandana Kataria; Chander Grover; Deepika Pandhi (Wolters Kluwer Medknow Publications, 2020)
We describe two siblings with diffuse, mutilating palmo-plantar keratoderma suggestive of Olmsted syndrome, with significantly compromised quality of life in the form of inability to walk and grasp objects. This was accompanied by severe pruritus and erythromelalgia-like symptoms. The keratoderma responded to acitretin therapy but there was paradoxical worsening of burning and pruritus which were further disabling. The poor response to medical and phototherapy in relieving these symptoms is described.